The Effect of Health Expenditure on Selected Maternal and Child Health Outcomes in Sub-Saharan African - Ashiabi, N.; Nketiah-Amponsah, E.; Senadza, B. (Emerald Group Publishing Limited, 2016)
Purpose The purpose of this paper is to investigate the effect of public and private health expenditures on selected maternal-child health outcomes in Sub-Saharan Africa (SSA). Design/methodology/approach The study utilizes panel data on 40 SSA countries spanning the period 2000-2010. The data are analyzed using the fixed effects estimation technique. Findings The results indicate that public health expenditure is inversely and significantly related to infant (IMRR) and under-five (U5MR) mortalities in SSA. Though public health expenditure has the a priori negative sign, it has no significant effect on maternal mortality (MMR) in SSA. Further, private health expenditure did not prove to be significant in improving maternal-child health outcomes (IMRR, U5MR and MMR) in SSA. Practical implications The implication of the findings is that a percentage point increase in public health expenditure (as a share of GDP) across the region will result in saving the lives of about 7,040 children every year. Hence, it is important for governments in SSA to increase their shares of health expenditure (public health expenditure) in order to achieve improved health outcomes. Originality/value Previous studies have not adequately explored the effect of various components of health expenditures – public and private – on health outcomes in the context of SSA. In addition to the focus on maternal-child health variables such as infant, under-five and maternal mortalities, the study accounts for the possibility of a non-linear and non-monotonic relationship between healthcare expenditures and health outcomes.
Keywords: Political economics; Health policy; Fixed effects; Governance; Health expenditure; Under-five mortality; Maternal mortality; E62; I15; I18